Turn‐Number‐Dependent Motion Behavior of Catalytic Helical Carbon Micro/Nanomotors. Issue 14 (14th May 2019) - Xu, Dandan; Zhan, Chen; Sun, Yanming; Dong, Zhijun; Wang, Guo Ping; Ma, Xing
Abstract: Helical micro/nanomotors (MNMs) can be propelled by external fields to swim through highly viscous fluids like complex biological environments, which promises miniaturized robotic tools to perform assigned tasks at small scales. However, the catalytic propulsion method, most widely adopted to drive MNMs, is seldom studied to actuate helical MNMs. Herein, we report catalytic helical carbon MNMs (CHCM) by sputtering Pt onto helical carbon nano‐coils (HCNC) that are in bulk prepared by a thermal chemical vapor deposition method. The Pt‐triggered H2 O2 decomposition can drive the MNMs by an electrokinetic mechanism. The MNMs demonstrate versatile motion behaviors including both directional propulsion and rotation depending on the turn number of the carbon helix. Besides, due to the ease of surface functionalization on carbon and other properties such as biocompatibility and photothermal effect, the helical carbon MNMs promise multifunctional applications for biomedical or environmental applications. Abstract : Helical carbon/Pt micro/nanomotors powered by Pt‐triggered H2 O2 decomposition have been constructed. This study demonstrates versatile motion behaviors dependent on the turn number of the carbon helix including both directional propulsion and rotation. The MNMs reported herein represent a new option to prepare and propel helical motors.